Implementation of the “Kurikulum Merdeka” in Learning Social Sciences in Junior High Schools - Andi Dewi Riang Tati (CV. ULIL ALBAB CORP, 2024)
This research aims to obtain observation data on how the Kurikulum Merdeka is implemented in the Social Sciences subject in history material in Junior High Schools. The research method used in this research is qualitative. To achieve this goal, researchers used data collection techniques through literature review. The data obtained from the research results were processed using qualitative analysis to determine the implementation of the “Kurikulum Merdeka” in social studies learning. Based on the research, it can be concluded that social studies learning activities in the “Kurikulum Merdeka” policy carried out by teachers have gone through three stages, namely: preliminary activities, core activities and closing activities. The third activity steps such as preliminary, core and closing learning have been fully implemented by the teacher, although at each learning step there are still activities that have not been implemented optimally. From the research results it is known that curriculum implementation is influenced by four variables, namely: communication, resources, disposition, and bureaucratic structure